Show that (b-acosC)sinA=acosAsinC

Dear Student,

L.H.S :- 

  Sin A                 1 - Cos A
-------------    x    --------------
1 + Cos A            1 - Cos A

=   Sin A - SinA.CosA
    ------------------------
          1 - Cos2 A

=   Sin ( 1 - Cos A )
    ----------------------
             Sin2 A
                                  ( This is because 1 - Cos2 A = Sin2 A ) & ( Further Sin A and Sin A will get cancel )
=  1 - Cos A
-----------------
      Sin A

=  R.H.S

Hope it helps...!!!!

  • -1
Hence proved
  • -1
Aryan sahu , I guess you are a loser . This question wasn't meant for people like you. So don't waste others' time
  • 1
Hope it’s satisfactory...

  • 2
What are you looking for?